Implementation of dextrose gel in the management of neonatal hypoglycaemia. (15th November 2016) - Ter, Marene; Halibullah, Ikhwan; Leung, Laura; Jacobs, Susan
Abstract : Aim: The aim of this study was to evaluate dextrose gel in the management of neonatal hypoglycaemia in the postnatal wards at an Australian tertiary level perinatal centre. Methods: An audit was performed before and after implementation of dextrose gel. Pre‐implementation, neonatal hypoglycaemia was managed with feed supplementation alone, and dextrose gel was used in addition to feed supplementation in the post‐implementation phase. Outcomes included admission to neonatal intensive care unit (NICU) for management of hypoglycaemia, proportion of neonates who achieved normoglycaemia (defined as blood glucose ≥2.6 mmol/L, with no clinical signs after one or two treatment attempts) and proportion of neonates with hypoglycaemia recurrence after normoglycaemia and one or two treatment attempts. Results: NICU admission for treatment of hypoglycaemia reduced significantly post‐implementation of dextrose gel (29/100 (29%) vs. 14/100 (14%), P = 0.01). No significant difference was seen in the proportion of neonates achieving normoglycaemia (71/100 (71%) vs. 75/100 (75%), P = 0.52), but hypoglycaemia recurrence was higher in the post‐implementation group (22/71 (31%) vs. 37/75 (49%), P = 0.02). Conclusions: Dextrose gel is effective in the management of neonatal hypoglycaemia in the postnatal ward setting, reducing admission to NICU and mother–infant separation.